Reduction of cyanide content of bitter almond and its oil using different treatments. (29th May 2019) - Zhang, Lingyan; Zhao, Min; Chen, Jia; Wang, Mengzhu; Yu, Xiuzhu
Summary: To reduce the cyanide content of bitter almond oil, four treatments were investigated. The optimal parameters were obtained, under which loss of cyanide of 79.4%, 87.2%, 98.3% and 98.4% were achieved for baking, microwave, water boiling and ultrasonic treatment, respectively. The effects of treatments on the physicochemical properties of bitter almond oil showed no significant differences. All treatments could reduce the cyanide content in bitter almond oil, and ultrasonic treatment was the most optimal treatment. The loss of cyanide was 98.4% when the ultrasonic power was 700 W for 50 min of treatment. Ultrasonic power and time had remarkable effect on the reduction of cyanide content. The proposed treatments could be applied to reduce the cyanide content in bitter almond oil. Abstract : Four treatments were optimized for the reduction of cyanide content in bitter almond and its oil. All treatments could reduce the cyanide content in bitter almond oil, and ultrasonic treatment was the most optimal treatment. No significant difference was found between physical and chemical characteristics of bitter almond oil among different treatments. These treatments are feasible alternatives for the reduction of cyanide content of bitter almond and its oil.